Dental malocclusions in the anterior sextant, in a group of Mexican patients between 3 and 14 years old. - José Murrieta-Pruneda; Dulce Varela-Ramírez; Araceli Rojano-Santillán; María Adriano-Anaya; Tomás Caudillo-Joya (Universidad de Concepción., 2020)
Aim: To evaluate the association between the frequency of malocclusions in the anterior sextant with dentition type, age, and sex. Material and methods: A descriptive, transversal and prospective study was carried out, in a convenience sample of 200 patients between 3 and 14 years old, of both sexes who attended the pediatric dentistry clinic of Dentistry Faculty from Autonomous University of Tlaxcala, Mexico. A dentist was standardized by a direct method (k=0.998, p=0.0001). Results: Crossbite and edge to edge bite were the most frequent (18% and 17% respectively), in no case the alterations in the previous sextant were related to sex, except altered overjet with age and dentition type (likelihood ratio=18,169, p=0.0001) (X2=18.820, p=0.0001). Conclusion: These observations highlight the importance of the diagnosis of possible alterations in the occlusion of the anterior sextant in both dentitions, in order to preventatively avoid major sequelae.